CD11b Regulates Fungal Outgrowth but Not Neutrophil Recruitment in a Mouse Model of Invasive Pulmonary Aspergillosis - Teschner, Daniel; Cholaszczyńska, Anna; Ries, Frederic; Beckert, Hendrik; Theobald, Matthias; Grabbe, Stephan; Radsak, Markus; Bros, Matthias (Frontiers in Immunology, 2019)
ß2 integrin receptors consist of an alpha subunit (CD11a-CD11d) and CD18 as the common beta subunit, and are differentially expressed by leukocytes. ß2 integrins are required for cell-cell interaction, transendothelial migration, uptake of opsonized pathogens, and cell signaling processes. Functional loss of CD18 - termed leukocyte-adhesion deficiency type 1 (LAD1) - results in an immunocompromised state characterized by frequent occurrence of severe infections. In immunosuppressed individuals Aspergillus fumigatus is a frequent cause of invasive pulmonary fungal infection, and often occurs in patients suffering from LAD1. Here, we asked for the importance of CD11b/CD18 also termed MAC-1 which is required for phagocytosis of opsonized A. fumigatus conidia by polymorphonuclear neutrophils (PMN) for control of pulmonary A. fumigatus infection. We show that CD11b-/- mice infected with A. fumigatus were unaffected in long term survival, similar to wild type (WT) mice. However, bronchoalveolar lavage (BAL) performed one day after infection revealed a higher lung infiltration of PMN in case of infected CD11b-/- mice than observed for WT mice. BAL derived from infected CD11b-/- mice also contained a higher amount of leukocyte-attracting CCL5 chemokine, but lower amounts of proinflammatory innate cytokines. In accordance, lung tissue of A. fumigatus infected CD11b-/- mice was characterized by lower cellular inflammation, and a higher fungal burden. In agreement, CD11b-/- PMN exerted lower phagocytic activity on serum-opsonized A. fumigatus conidia than WT PMN in vitro. Our study shows that MAC-1 is required for effective clearance of A. fumigatus by infiltrating PMN, and the establishment of an inflammatory microenvironment in infected lung. Enhanced infiltration of CD11b-/- PMN may serve to compensate impaired PMN function.